Empowering communities or delinquent congregations? A study of complexity and contradiction in Canadian youth cultures and leisure spaces - Wilson, Brian S. (My University, 1999)
This dissertation is a theoretical and empirical examination of youth culture in Canada. Theoretically, a continuum of youth-related cultural theories was devised, and a framework that integrated critical interactionism, structuralism, and postmodern theory was adopted. Empirically, the need for more qualitative research on youth culture in Canada was identified and subsequently engaged through the presentation of two ethnographic case studies that were undertaken on this topic. The first case was a study of the rave subculture in Toronto--a "middle class" culture of youth renowned for drug-use, an interest in computer-generated music, and attendance at all-night "rave" dance parties. The second case was a study of youth in an urban recreation/drop-in centre in a low-income area in southern Ontario. These groups were chosen because of their similar and distinct positionings in relation to social class, strategies of resistance, a (relatively) postmodern context, and urban social spaces. Key components of the rave study included: (a) findings that "rave" was defined by its wide range of forms and characteristics--a range that existed simultaneously across the subculture (e.g., in various raver sub-communities), across the careers of individual ravers (e.g., a loss of idealism about rave's potential as a resistant culture), and across the "life" of the Canadian rave scene (e.g., the scene's evolution); (b) the development of "five theses on resistance" as a framework for understanding the multiple, often contradictory positionings of raver youth; and (c) the adoption of Best and Luckenbill's (1994) model of organizational sophistication as means to conceptualize the "local and global" culture. The youth centre study included findings that: (a) despite a broader context of "risk" outside the centre, youth maintained an informal culture of nonviolence by creating "tolerance rules" that allowed diverse groups to coexist; (b) the youth-driven informal culture of the centre allowed youth to maintain a sense of power in an organization otherwise dominated (administratively) by adults; (c) experiences within the centre, while generally positive, were varied and extremely gendered, with female youth being marginalized in the informal, male-dominated sport culture; (d) among female youth, there existed simultaneously a resistance to broader gender/class based limitations on sport participation, and a reproduction of informal power structures. The dissertation concluded with a discussion of the demonstrated importance/implications of being attentive to complexity in the study of youth culture in Canada.
Keywords: Sociology; Sociology